Eksplorasi Suku Arecaceae di Hutan Durin Serugun Kecamatan Sibolangit Kabupaten Deli Serdang Sumatera Utara - Purba, Nadia Puspita Sari; Sari, Wina Dyah Puspita; Ritonga, Yusron Efendi (Jurnal Biosilampari : Jurnal Biologi, 2025)
The Arecaceae family is a group of monocotyledonous plants with significant ecological and economic value, widely used by communities in tropical regions, including North Sumatra. This study aimed to explore, identify, and describe the utilization of Arecaceae species by the local community in the Durin Serugun Forest, Sibolangit District, Deli Serdang Regency. The research was conducted from April to June 2025 using an exploratory method with purposive sampling, direct morphological observation, and semi-structured interviews. Data were collected through three forest tracking routes and analyzed descriptively. The study identified 17 Arecaceae species from 10 genera, dominated by the genus Calamus. Morphological characteristics were observed based on stem, leaf, tendril, flower, and fruit structures. These species were found growing in diverse habitats ranging from rocky slopes to moist areas under tropical forest canopies. The Karo ethnic community utilizes these plants for food, building materials, traditional medicine, and ritual purposes. Plant parts used include stems, leaves, flowers, and fruits. This study provides essential information for documenting local biodiversity and serves as a foundation for conservation efforts and the sustainable use of plant resources, particularly Arecaceae species in North Sumatra.